Factors Influencing Quality of Life in Colorectal Cancer Patients with a Stoma during the First 6 Months after Surgery. - Yang, Bicong; Chantamit-O-Pas, Chutima; Hengudomsub, Pornpat (Korean Journal of Adult Nursing, 2026)
Purpose: This study aimed to identify predictors of quality of life (QoL), including self-efficacy, social support, illness perceptions, and resilience, among colorectal cancer patients during the first 1 to 6 months after stoma surgery. Methods: A predictive correlational design was used with 142 adult patients who had undergone stoma surgery within the preceding 1 to 6 months. Data were collected using validated instruments measuring QoL, self-efficacy, social support, illness perceptions, and resilience. The data were analyzed using descriptive statistics, the independent t-test, one-way analysis of variance, the Games-Howell post-hoc test, Pearson correlation coefficients, and hierarchical multiple linear regression analysis. Results: The participants had a mean age of 56.15 years (standard deviation, 6.51 years); 67.6% were male, and 57.0% had a temporary stoma. In model 1, the method of paying medical expenses significantly predicted QoL, explaining 6.0% of the variance (adjusted R²=.06, p=.006), with self-financed patients reporting lower QoL than insured patients. In model 2, the addition of psychosocial variables (self-efficacy, social support, illness perceptions, and resilience) substantially improved the model, explaining 70.0% of the variance (adjusted R²=.70, p<.001). In the final model, illness perceptions (β= -.61), social support (β=.32), resilience (β=.20), and self-efficacy (β=.19) were significant predictors (all p<.001), whereas method of paying medical expenses was no longer significant. Conclusion: This study provides evidence to support the development of interventions targeting illness perceptions, social support, resilience, and self-efficacy to improve QoL among stoma patients during the early postoperative period.